Optimización del proceso de separación de chocho. - Chuquitarco Chiluisa, Luis Miguel (2019)
The present proposal establishes a prototype of machine in order to chocho optimization separation process directed to the small producers and merchants of the product. The prototype of machine fulfills with the process of separating the best and worst chocho, additional classifying according to its size, rating by its quality. Indirectly it would reduce the number of people that do this activity, that´s because is a hand-work process that requires personal training, with repetitive movements. This activity affect their hands, wrist, fingers and force people to keep the same rigid position for a long periods of time affecting principally the spine. With the proposal, the workforce will be reduced and these people would do other activities. According to the existing problem, different solution alternatives were established in order to obtain encouraging results to achieve the optimization of the separation process. It was established three available alternatives, the first one was to obtain the product classified through a vibrating table that separates the product by its size, but no by its quality that is why a new alternative needed. The second alternative an open air source was added; it was located, so that when the product falls, go through it. After many tests carried out the separation was achieved and visually was appreciated that the good quality product comes out with the bad one, finally the conclusion was that the results weren´t expected. The third and last alternative was to implement a closed system for air circulation, with this the results were better, the process was visually validated obtaining a product separated by its size and quality. The prototype of machine was built considering that it will work with food, it was made of stainless steel and material composed of aluminum. The built prototype performs the separation of good and bad chochos allowing the optimization of used resources in the process; additional the involved people in the process are just for filling up the machine in the chute alimentation, picking the product and subsequent storage.